Enhanced Spatial Pyramid Pooling And Intersection Over Union In Yolov4 For Real-time Grocery Recognition System - Saqib Jamal Syed; Putra Sumari; Hailiza Kamarulhaili; Valliappan Raman; Wan Rahiman; Sundresan A/L Perumal (Journal of Theoretical and Applied Information Tec, 2024)
Indexed by Scopus/ERA